Clinicopathological evaluation of abnormal uterine bleeding in perimenopausal women - Lotha, Lithingo; Borah, Asha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Abnormal uterine bleeding is considered as one of the most common and challenging problem presenting to the gynecologist. It is responsible for as many as one third of all outpatient gynaecological visits. This study was carried out in the department of Obstetrics and Gynaecology, Assam Medical College and Hospital, Dibrugarh to evaluate clinically gynaecological causes and the endometrial pattern of abnormal uterine bleeding in perimenopausal women. Methods: This is a retrospective study of 148 perimenopausal women with complain of abnormal uterine bleeding in the age group ranging from 40-50 years for a period of one year from 01 November 2014 to 30 November 2015. The age, parity, menstrual complaints were noted and clinical diagnosis with ultrasound report and histopathological reports (of endometrial tissue) were analyzed. Finally the histopathological report of the hysterectomy specimen was correlated. Results: Menorrhagia was the commonest complaint. AUB was seen more in multiparous women (64.8%). Fibroid uterus was the commonest cause which is 52.7% followed by DUB 41.2%, adenomyosis 4.7%, and uterine malignancy 1.3%. Conclusions: Clinicopathological evaluation of AUB showed that fibroid uterus followed by DUB is the most common cause in perimenopausal women. Occurrences of endometrial hyperplasia increases in perimenopause which is of great value as it is a forerunner of carcinoma.